Pendekatan Konstruktivis dalam Kajian Diplomasi Publik Indonesia - Rachmawati, Iva (Universitas Muhammadiyah Yogyakarta, 2016)
Rationalist approach remains dominant in the research of Indonesian public diplomacy. Therefore, public diplomacy is always used as a tool to gain the national interests through a particular image. In such framing, all activities in public diplomacy are intended for the stateâ€™s positive image. Besides, Rationalist still puts state as the main actor in public diplomacy. Domestic dimension did not have the same position as the state in interpreting international phenomena. Whereas, each actor has the same access to information and communication nowadays. Rationalist has given dialogue as an important contribution to public diplomacy strategy. Dialogue is one of the communication forms which have a capability to build trust between actors. Several problems in limiting the development of public diplomacy concept become a reference for proposing Constructivist as an alternative approach. This approach will help understanding public diplomacy more by putting the consciousness of the difference of national identity and relationship building as the main purposes. Several empirical studies showed that national identity preservation had already held by not only a state but also domestic dimension. This approach will give domestic dimension a wider room in public diplomacy as well as the state in interpreting international phenomenon.Â Dalam kajian-kajian diplomasi publik Indonesia, pendekatan rasionalis masih merupakan pendekatan yang dominan. Akibatnya, diplomasi publik selalu diletakkan sebagai alat untuk meraih kepentingan nasional melalui citra tertentu. Pembingkaian diplomasi publik semacam ini mengarahkan sejumlah kegiatan yang dilakukan dalam diplomasi publik semata-mata demi meraih citra positif negara tersebut. Di samping itu, pendekatan ini juga masih menempatkan negara sebagai aktor utama dalam diplomasi publik. Dimensi domestik belum mendapat tempat sebagai aktor yang sejajar dalam menginterpretasi fenomena antar negara. Sementara itu pada kenyataannya, setiap aktor memiliki akses yang sama dalam informasi dan komunikasi. Rasionalis memang telah memberi kontribusi penting dalam strategi dalam diplomasi publik, yaitu dialog, dimana komunikasi dalam bentuk dialog mampu menumbuhkan kepercayaan antar aktor. Beberapa hal yang dirasa membatasi perkembangan konsepsi diplomasi publik menjadi rujukan melalui artikel ini untuk mengusulkan pendekatan Konstruktivis dalam memahami diplomasi publik. Pendekatan tersebut meletakkan kesadaran atas perbedaan identitas nasional dan relationship building sebagai tujuan utamanya. Beberapa kajian empiris menunjukkan bahwa upaya memelihara identitas nasional telah dilakukan oleh tidak saja negara tetapi juga dimensi domestik. Dengan demikian, pendekatan ini memberikan ruang bagi dimensi domestik sebagai aktor di samping negara dalam diplomasi publik